Algunas reflexiones sobre el profesor como “piedra de toque” - León, Ramón (2024)
The present article presents a series of reflections on the role of teachers in contemporary society, marked by rapid transformations. Although teachers are recognized as key figures in the socialization process, their social image often goes unrecognized, as do their salaries. This happens despite the challenges they face, stemming from the massification of student bodies, the emergence of new technologies, and scientific advancements, which require constant updating and a critical stance towards their own work. At the same time, “old” qualities such as punctuality, respectful treatment of students, and professional ethics remain essential. Didactic innovation, the incorporation of new knowledge, and commitment to the profession are fundamental pillars for achieving excellence in the educational field.